A multimedia computational aid to gas turbine design teaching - Ramsden, K. W. (Cranfield University, 1995)
The ambitions of the teacher to fully prepare engineering students for the working environment are usually limited by the length of the lecture course. Consequently, few opportunities exist in the learning process for the student to gain experience in both design and design-optimisation. This document describes a suite of integrated personal computer based programmes designed to illustrate many important aspects of gas turbine component design and overall performance estimation for use both inside and outside the classroom. Accordingly, the objectives of the programmes are to provide a broad understanding of the whole engine and its major components by enabling the following: o a rapid and in depth method for the assessment of design point, off design and deteriorated performance principles for a wide range of gas turbine types and applications. a demonstration of the needs and implications of performance compromise arising from design constraints. a demonstration of how the design and performance limitations imposed by one component influence others. a demonstration of the design compromises required by the interactions between the disciplines of aerodynamics, thermodynamics and mechanical integrity. O O O When used in conjunction with a programme of lectures, tutorials, case studies, and computer based workshops, the new software enables a rapid and in depth understanding of gas turbine performance and component design. ln addition, the programme suite has extensive general application to gas turbine overall performance assessment and to the preliminary design of compressors and turbines.